Formulating Resveratrol and Melatonin Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) for Ocular Administration Using Design of Experiments - Elide Zingale; Angela Bonaccorso; Agata Grazia D'Amico; Rosamaria Lombardo; Velia D'Agata; Jarkko Rautio; Rosario Pignatello (MDPI AG, 2024)
Recent studies have demonstrated that Sirtuin-1 (SIRT-1)-activating molecules exert a protective role in degenerative ocular diseases. However, these molecules hardly reach the back of the eye due to poor solubility in aqueous environments and low bioavailability after topical application on the eye's surface. Such hindrances, combined with stability issues, call for the need for innovative delivery strategies. Within this context, the development of self-nanoemulsifying drug delivery systems (SNEDDS) for SIRT-1 delivery can represent a promising approach. The aim of the work was to design and optimize SNEDDS for the ocular delivery of two natural SIRT-1 agonists, resveratrol (RSV) and melatonin (MEL), with potential implications for treating diabetic retinopathy. Pre-formulation studies were performed by a Design of Experiment (DoE) approach to construct the ternary phase diagram. The optimization phase was carried out using Response Surface Methodology (RSM). Four types of SNEDDS consisting of different surfactants (Tween® 80, Tween® 20, Solutol® HS15, and Cremophor® EL) were optimized to achieve the best physico-chemical parameters for ocular application. Stability tests indicated that SNEDDS produced with Tween® 80 was the formulation that best preserved the stability of molecules, and so it was, therefore, selected for further technological studies. The optimized formulation was prepared with Capryol® PGMC, Tween® 80, and Transcutol® P and loaded with RSV or MEL. The SNEDDS were evaluated for other parameters, such as the mean size (found to be ˂50 nm), size homogeneity (PDI < 0.2), emulsion time (around 40 s), transparency, drug content (>90%), mucoadhesion strength, in vitro drug release, pH and osmolarity, stability to dilution, and cloud point. Finally, an in vitro evaluation was performed on a rabbit corneal epithelial cell line (SIRC) to assess their cytocompatibility. The overall results suggest that SNEDDS can be used as promising nanocarriers for the ocular drug delivery of RSV and MEL.